ENMD-1068 inhibits liver fibrosis through attenuation of TGF-β1/Smad2/3 signaling in mice - Quan Sun (Nature Portfolio, 2017)
Abstract Protease-activated receptor 2 (PAR-2) plays an important role in the pathogenesis of liver fibrosis. We studied the effect of N1-3-methylbutyryl-N4-6-aminohexanoyl-piperazine (ENMD-1068), a PAR-2 antagonist, on the development of CCl4-induced liver fibrosis in mice and activation of hepatic stellate cells (HSCs) isolated from the mice. Before CCl4 injection, the mice were injected intraperitoneally with either 25 mg/kg or 50 mg/kg ENMD-1068 or with 200 μL of the vehicle control twice per week for 4 weeks. The isolated HSCs were stimulated by TGF-β1 with or without ENMD-1068 to evaluate the role of PAR-2 in TGF-β1 induced HSCs activation and collagen production. We showed that the levels of ALT/AST, collagen content, and α-smooth muscle actin (α-SMA) were significantly reduced by treatment with ENMD-1068 in CCl4-induced fibrotic mice. Interestingly, we found TGF-β1 signaling-related expression levels of α-SMA, type I and III collagen, and C-terminal phosphorylation of Smad2/3 were significantly decreased in the ENMD-1068 treated HSCs. Moreover, we showed ENMD-1068 treatment inhibited trypsin or SLIGRL-NH2 stimulated calcium release and TGF-β1 induced Smad transcriptional activity in HSCs. We demonstrated that ENMD-1068 reduces HSCs activation and collagen expression through the inhibiton of TGF-β1/Smad signal transduction.